Short review of ultrafiltration of polymer membrane as a self-cleaning and antifouling in the wastewater system - Mohamad, Siti Hawa (2013)
This paper focuses on ultrafiltration polymer membrane for wastewater systems as a self-cleaning and antifouling. Fouling is one of the most important problems in almost all membrane processes. In this review, membrane antifouling and self-cleaning properties can be improved by using titanium dioxide (TiO2) particles and UV radiation on membrane structure and surface. Coating TiO2 particles on membrane surface is an advanced method to minimize membrane fouling. Hence, these properties can be improved the membrane performance.